Nghiên cứu ảnh hưởng của một số thông số tới quá trình trùng hợp ghép metacrylic axit và metyl metacrylat bằng phương pháp trùng hợp nhũ tương - Thắng, Trần Vũ; Thu Hà, Phạm Thị; Khôi, Nguyễn Văn; Mạnh, Nguyễn Văn; Đức, Nguyễn Trung (Vietnam Journal of Chemistry, 2015)
Some effects of emulsifier to methacrylic acid (MAA) and methyl methacrylate (MMA) copolymerization was studied. The emulsion polymerization was prepared in water medium and used to amoniumpersulphate as innitor. The stability of emulsion was investigated by class, concentration of emulsifier and reaction temperature, monomer concentration and size particle. The results show that nonyl phenol ethoxylate (NP9) emulsifier concentration was 3 % at 70 oC reaction temperature with 30 % monomers concentration.